Alpha hemoglobinophaties in Rosario, Argentina - Ojeda, Mara Jorgelina (2016)
Hemoglobinopathies are the most common recessive diseases worldwide. While the molecular basis of β-thalassemia in Rosario has been addressed, that of α-thalassemia and α structural alterations, has not. In this study 105 individuals from different families referred to our center were investigated for alpha hemoglobinopathies because of low MCV (15%. Six of them with a clinical phenotype of thalassemia intermedia were diagnosed as Hb H disease (five cases) and Hb H like (one case). It also included one patient with sickle cell trait, confirmed by hematological and molecular studies. We were able to identify alpha globin genes mutations in 92 individuals (87.6%): 88 patients with alpha thalassemia, 3 patients with structural alterations and one with both. In total, 13 individuals (12.4%) had no identified α-globin mutation. This study is the first to deal with the molecular basis of α-hemoglobinophaties in Rosario.